THE MODEL OF COMPETITIVE ADVANTAGE OF SPECIFIC RESOURCES AND SUSTAINABLE DEVELOPMENT OF TOURIST DESTINATIONS - Tatyana Alexandrovna Shebzukhova; Lyudmila Nikolaevna Koval; Anna Petrovna Babchenko (Современная наука и инновации)
The quadrangular model of competitive advantage of tourist destinations of the North Caucasus regions was constructed